Declining Economic Opportunity and a Shrinking Safety Net: Consequences for Maine - LaRochelle, Ryan (Maine Policy Review, 2020)
Ryan LaRochelle discusses the consequences of declining economic opportunity and a shrinking social safety net for Maine. LaRochelle recommends that policymakers in Augusta recognize how precarious many Mainers’ economic situations are and take action.
Keywords: inequality; insecurity; poverty-reduction efforts; SNAP; Social Security